(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Aquatic life is influenced by physicochemical parameters which enabled organisms to develop different adaptations that may improve and sustain the productivity of the ecosystem. Changes in the water quality may affect biotic community structure with the most vulnerable species dying while the most sensitive ones act as bio- indicators of environmental health. This paper assessed some physicochemical parameters on the abundance and distribution of mosquito larvae in River Antau conducted between April and July, 2021. The samples were collected from three selected points (A, B and C) monthly using dipper and larvae bowl and transported to the Entomology and Insectary Laboratory for analysis. Temperature, pH and DO across the sampling points were equally analyzed. A total of one thousand and three (1003) mosquito larvae including Anopheles sp 562(56.0%) and Culex sp 441(44.0%) were collected. The results showed that the highest number of Anopheles sp 386(68.7%) were recorded in May and the lowest 34(6.1%) in June, while the highest number of Culex sp152 (34.5%) were encountered in April and the lowest 40 (9.1%) occurred in the month of July. Physicochemical parameters were found to influence the distribution and abundance of mosquito larvae in River Antau. This study recommends for public health awareness on the mosquito’s management and control to reduce transmission of malaria in the area